1-Methyltryptophan Modifies Apoplast Content in Tomato Plants Improving Resistance Against Pseudomonas syringae - Scalschi, Loredana; Llorens, Eugenio; González-Hernández, Ana I.; Valcárcel, Mercedes; Gamir, Jordi; García-Agustín, Pilar; Vicedo, Begonya; Camañes, Gemma (Frontiers in Microbiology, 2018)
Abstract Plants are able to produce numerous natural products, many of which have been shown to confer protection against microbial attack. In this way, we identified 1-methyltryptophan (1-MT), a natural compound produced by tomato plants in response to Pseudomonas syringae attack, whose application by soil drench provided protection against this pathogen. In the present work, we have studied the mechanisms underlying this protection. The results demonstrated that 1-MT can be considered a new activator of plant defence responses that acts by inhibiting stomatal opening produced by coronatine (COR), which could prevent bacteria entering the mesophyll. Besides, 1-MT acts by blocking the jasmonic acid (JA) pathway, which could avoid manipulation of the salicylic acid (SA) pathway by a bacterium, and thus hinder its growth. Although no antimicrobial effect at the concentration detected in the plant was observed, we cannot rule out a role of 1-MT by itself because it affects the expression of the fliC gene, involved in the synthesis of flagellum, and produces reduced bacterium motility and, therefore, its infective capacity. The results highlight the effect of a tryptophan derivative on induced resistance in plants.